Prospect Theory in Mutual Funds : Effects on mutual funds’ performance and cash flows - Kikari, Anniina (My University, 2026)
The purpose of this thesis is to investigate whether the prospect theory can explain fund flows and performance of mutual funds. Through a literature review, this thesis finds that, especially with retail investors, prospect theory is noticed through their loss aversion and overweighting of small probabilities of extreme results. These lead to cash flows to funds that are considered valuable by prospects to investors, and cash flows out of funds that are not. Financial professionals are less susceptible to extreme loss aversion, but this thesis still finds evidence of portfolio managers behaving according to certain aspects of prospect theory.

Tämän opinnäytetyön tarkoituksena on selvittää, voiko prospektiteoria selittää sijoitusrahaston rahavirtoja ja sijoitusrahastojen suorituskykyä. Kirjallisuuskatsauksena tämä tutkielma toteaa, että etenkin yksityissijoittajien kohdalla prospektiteoria huomataan heidän tappiovastenmielisyydestään ja äärimmäisten tuottojen pienten todennäköisyyksien ylipainotuksesta. Nämä lisäävät rahavirtoja rahastoihin, joita sijoittajat pitävät arvokkaina mahdollisuuksien puolesta, ja pois rahastoista, joita sijoittajat eivät koe arvokkaina. Rahoitusalan ammattilaiset ovat vähemmän alttiita äärimmäiselle tappioiden vastenmielisyydelle, mutta tämä tutkielma löytää silti todisteita siitä, että salkunhoitajat käyttäytyvät prospektiteorian tiettyjen näkökulmien mukaisesti.
Keywords: mutual funds; investors; decision making; funds (organisations); investments (economics); finance; investment companies; investments; securities portfolios; investment funds; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|